ANALISIS PENGARUH EFISIENSI MANAJEMEN, UKURAN BANK, KECUKUPAN MODAL, FINANCING TO DEPOSIT RATIO (FDR), DAN PROFITABILITAS TERHADAP PEMBIAYAAN BERMASALAH (Studi Kasus pada Bank Umum Syariah di Indonesia Periode Tahun 2011 – 2016 ) - Agustin, Melinda; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2017)
This research aims to determine how big the influence of the specific variables of the bank are the efficiency of management, size, financing to deposit ratio (FDR), capital adequacy, and profitability to financing problem of sharia banks in Indonesia on period 2011 to 2016. This research is done by purposive sampling method. The sample used are 7 sharia commercial banks in Indonesia. The data used are quarterly bank reports obtained from each website of sharia bank which is used as research sample. Multiple linear regression analysis was used in this study. This study uses computer software program SPSS 23. The results showed that all of independent variables used significantly affected the financing problem of sharia banks. Variable management efficiency, capital adequacy and profitability have a significant negative effect on financing problem. Financing to Deposit Ratio is the only variable has not significant effect on financing problem. The variable of bank size is the only independent variable that has a significant positive effect on financing problem. In this study, the adjusted R square has a high enough value of 0.297, which means 29,7% of the predicted NPF change of the five variables, while the remaining 70.3% is predicted by other variables outside the research model.